Tradisi Ziarah Makam Keramat Habib Abdullah bin Ali Al-Haddad Sangeng Bangil: Tinjauan Sejarah Kebudayaan - Rahmadi, Noor Ali; Hasib, Kholili; Rahman, Abdur (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
The tradition of visiting graves is a form of religious expression that has developed in various Muslim communities, especially in Indonesia. One of the tombs that has sacred meaning is Habib Abdullah Al-Haddad Sangeng in Bangil which is very deep. Apart from being a final resting place, this tomb also has symbolic meaning as a meeting point between Islamic values ​​brought from Hadramaut and local culture in Indonesia. This research aims to understand how this tradition was formed, the values ​​contained in it, and the role of sacred graves in the socio-religious dynamics of the local community. The research method used is a historical-cultural approach by examining various historical sources, interviews with community leaders, and direct observation at the grave site. The research results show that the grave of Habib Abdullah Bin Ali Al-Haddad has become a pilgrimage center for Muslim communities, not only from Bangil but also from various other regions in Indonesia. Belief in the blessings (barakah) of this tomb is one of the main factors that encourages people to make pilgrimages, perform prayers, and participate in various rituals that have been going on for generations. Apart from the religious aspect, this tradition also has social and cultural dimensions that strengthen community ties, both through religious, economic activities and social interactions that occur during pilgrimage processions. Thus, pilgrimage to sacred graves not only functions as a practice of worship but also as a means of preserving Islamic cultural heritage in the archipelago. This research provides new insight into the importance of sacred graves in shaping the religious and social identity of Muslim communities in Indonesia.